Physical and mechanical evaluation of bricks of soil-cement-rice husk mixtures - da Silva Milani, Ana Paula; Freire, Wesley Jorge (Revista Ingeniería de Construcción, 2005)
This work informs about a research effort with the aim of proposing construction solutions that help reducing the environmental degradation the research studied the utilization of rice husk added to mixtures of soil and cement to obtain an alternative construction material. For this purpose, the soil was treated with different amounts of cement and rice husk and then the physical and mechanical properties of each mix were studied. The rice husk preparation consisted of grinding, sieving, and pre-treatment with a lime solution followed by physical analysis in laboratory conditions. The different mixtures of soil, cement and rice husk were tested for Proctor compaction, unconfined compression and splitting tensile strength at the age of 7 and 28 days as well as to water absorption. The soil-cement-husk mixtures presenting the best results in terms of mechanical strength were utilized for specimen brick manufacturing. Compressive strength tests at the age of 7, 28 and 60 days were applied to the specimens and the water absorption was measured. The obtained data was then statistically analyzed and the results showed that the sandy soil with the addition of 12% of the cement and rice husk combination was the best treatment in terms of physical and mechanical properties, pointing out its promising use as an alternative material for brick be used in rural construction.